DAPATKAH INDONESIA BEBAS DARI KUTUKAN KOLONIAL? REFLEKSI KRITIS ATAS MP3EI - Noer Fauzi Rachman & Dian Yanuardy (Jurnal Ilmu Sosial Mamangan, 2014)
This paper seeks to analyze critically the so-called Master Plan for the Acceleration and Expansion of Indonesian Economic Development (MP3EI)--- a newly development master plan launched in 2011 during Susilo Bambang Yudhoyono administration. MP3EI introduced some keywords such as "economic corridors", "Focused Investment Zones", "connectivity", "infrastructure development", and so forth. This paper intends to unpack the origins and paradigm of MP3EI by tracing and analyzing "Comprehensive Asia Development Plan" (CADP)--- a document which was launched in 2009 by the Economic Research Institute for ASEAN and East Asia (ERIA). This paper shows that MP3EI is a framework and development design based on consesionary policy, infrastructure development projects as service links, and the dispersion of industrial zones in Indonesia. Finally, the writers argue that the current development model promoted by MP3EI is a colonial curse.